Loan to value ratio and monetary transmission mechanism - Vlastimil Reichel; Daniel Němec; Jakub Chalmovianský (DANUBE: Law, Economics and Social Issues Review, 2019)
Using a dynamic stochastic general equilibrium model (DSGE) with the housing sector, this paper evaluates the impact of housing collateral on the business cycle in the Czech economy. We devote special attention to the setting of the loan to value (LTV) ratio, which we believe plays an important role as a regulator of the monetary transmission mechanism. The impacts of LTV ratio are quantified by simulating the responses of alternative LTV level setting on key macroeconomic variables. Our simulations are based on an estimated DSGE model. Our approach allows us to understand better the responses of the real economy to the tightening of monetary policy moderated by different LTV levels. Our results show that higher loan to value ratios strengthen the effect of the monetary transmission mechanism to consumption and output.
Keywords: 330; Housing Sector; Loan to Value Ratio; DSGE Model; Monetary Transmission Mechanism; Czech Republic